The Domestic Origins of Sudan’s External Debt Crisis - Abdel Rahman, Abdel Rahman Ahmed (Intellectual Discourse, 1995)
Domestic factors played a significant role in Sudan’s external debt crisis which emerged in the early 1980’s. Personal rule and related political survival considerations undermined on-going economic adjustment programmes and prompted heavy external borrowing. Borrowing from abroad went unchecked because of the absence of an effective debt management system. It was also fuelled by economic corruption and the decline of cotton, Sudan’s principal export crop. The absence of an effective debt management mechanism and economic corruption were a product of the lack of political and fiscal accountability in the context of personal rule.